Transformasi Pemahaman Hadis Tata Cara Rukuk dan Sujud Bagi Perempuan - Amirul Fikri Hanif; Yulia Rahmi (Pusat Riset dan Inovasi Nasional, 2024)
The whole series of prayer movements are arranged in a tauqifi manner taught and practiced by the Prophet SAW. There is no information found in the Prophetic traditions that explain the differences in prayer movements between men and women. In the practice that developed in the community, there was an understanding that there were differences in ruku' and prostration movements for women. Where it is understood that for women to close their hands to their limbs, the distinction appears as a transformation of understanding of the hadith which then becomes a religious practice in the community which is conveyed and taught until it is accepted by the community as a form of teaching. This will then be studied in the form of its transformation from the hadith text into practice in the community. This discussion will be examined with a literature study approach that refers to works in the field of hadith to trace the understanding that emerged in each period. The hadith literature shows that there is a narration in the Musnad of Abu Hanifah that appeared at the beginning of the second century, which hints at a different way of praying for women by closing their limbs. This narration was not popular in the mu'tamad hadith books that appeared until the end of the third century A.H. Based on this. In the fourth century, another understanding emerged based on a narration that explains bowing and prostration in a way that is specific to women. The narration was found in Sunan Kubra al-Bayhaqy, where al-Bayhaqy was a follower of the Shafi'iyyah school of thought. This understanding developed in the books of fiqh shafi'iyyah which were widely used in pesantren and became the understanding and practice of the majority of people who followed the Shafi'i school of thought.